(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
Professor Allman exhibited some artefacts unearthed near the Swiss Lakes and in the valley of the Somme, arguing that the artefacts found in the Somme valley were older than those from the Lakes. However, other members of the Society disagree, suggesting that there may have been other factors such as the environment of the Somme valley and available building materials that contributed to the difference in the artefacts.